2011
DOI: 10.3382/ps.2010-01018
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcriptomic study of vitamin E and an algae-based antioxidant as antioxidative agents: Investigation of replacing vitamin E with the algae-based antioxidant in broiler diets

Abstract: Previous study indicated that inclusion of an algae-based antioxidant as an antioxidative agent [EconomasE, Alltech, Nicholasville, KY; EcoE] significantly reduced the amount of vitamin E (VE) required in broiler diets without compromising performance and meat quality. To assess the mechanisms related to the VE-saving activity of EcoE, as well as other potential functions related to EcoE and VE supplementation, we analyzed gene expression profiles of breast muscle from broilers fed a control diet, the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
20
0
2
Order By: Relevance
“…Similarly, Kaiser et al (2012) stated that vitamin E containing diet can enhance the immune protection against bacterial lipopolysaccharide associated infection in chicken. Nutrigenomics data analysis also showed that algae based diet can reduce the stress profile in chicken through nutrigenomics data analysis (Xiao et al, 2011). Like vitamin E, different types of minerals such as zinc can actively regulates the transporter gene in intestine of broiler chicken and the expression pattern is directly related to the amount of zinc in feed.…”
Section: Application Of Nutrigenomics In Animal Sectormentioning
confidence: 99%
“…Similarly, Kaiser et al (2012) stated that vitamin E containing diet can enhance the immune protection against bacterial lipopolysaccharide associated infection in chicken. Nutrigenomics data analysis also showed that algae based diet can reduce the stress profile in chicken through nutrigenomics data analysis (Xiao et al, 2011). Like vitamin E, different types of minerals such as zinc can actively regulates the transporter gene in intestine of broiler chicken and the expression pattern is directly related to the amount of zinc in feed.…”
Section: Application Of Nutrigenomics In Animal Sectormentioning
confidence: 99%
“…Also in animal production, VE is extensively applied to improve growth, reproductive performance, feed efficiency and preferred meat product quality. A transcriptome study in broilers [21] compared the genome wide gene expression profiles of breast muscle from chicks fed vitamin E and an algae-based antioxidant diets. This study found differential expression in transcriptional profiling between the two diets and identified gene networks that likely play key roles related to nutriphysiological functions of vitamin E. In a more recent study [20], different dietary supplementations with Vitamin E (VE) and different inclusion levels of grape pomace (GP) vs an un supplemented control group were compared to study their effects on the expression of candidate genes involved in oxidation and lipid metabolism in broiler muscle.…”
Section: Studies Of Supplementation With Vitaminsmentioning
confidence: 99%
“…Early steps in this direction have been presented by Xiao et al (2010). This study looked at the molecular mechanisms comparison of two fractions from the yeast cell wall.…”
Section: Modulating Immunity and Effect On Mucin Dynamicsmentioning
confidence: 99%